Continous fibre optic components utilizing evanescent coupling to organic thin films - Charters, R. B. (Cranfield University, 1995)
The following thesis is conceded with single mode fibre optic components which exhibit a wavelength selective transmission response. The response is achieved by mechanically polishing the side of a optical fibre in order to asymrnetrically remove a large proportion of the cladding material, and access the evanescent field of the propagating lightwave. Resonant interaction between the fibre guided mode and a multimode planar waveguide, deposited directly onto the polished interaction region, impacts a wavelength selective response to the fibre transmission. A theoretical model is developed to describe device performance, and the structure is fully investigated as a function of the experimentally controllable parameters. A experimental characterization of device performance is undertaken and found to be in good agreement with the theoretical predictions. Methods of depositing organic films directly onto side polished fibres are then considered, and it is demonstrated that both the dip coating and spin coating of photoresist films produces solid state devices with 3dB linewidths as narrow as 7.0nm and insertion losses consistantly less than O.2dB. The thenno-optic nature of the overlays is also demonstrated to allow wavelength tunability of the device responses, exhibiting a linear sensitivity of AÄ3/AT = -0.6mn/°C. This could be exploited as the basis of a temperature sensor. The addition of a bulk silver superstrate is then shown to provide a modulation depth enhancement of 7.6dB for the TM polarization state, with negligible increase in linewidth. The Langmuir-Blodgett (LB) technique is investigated as a means of accurately fabricating single mode overlays, and in-situ measurements of the deposition of co-tricosenoic acid films reveals a strong dependence of transmission response upon lm thickness (AÄ0/Ad = 2.4) for this overlay mode order. Through the use of a annular polishing technique, the repeatability of the LB process can be greatly increased and it is found that this method allows the deposition of more complex films. Finally, the possibility of amplitude modulation is considered through the use of D-rr-A LB lm forming molecules.